KNOWLEDGES OF FERTILIZED WOMEN ABOUT THE VISUAL INSPECTION OF ACETIC ACID - Deswita, Deswita (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Kemenkes Riau, 2020)
Cervical Cancer or Uterine Carcinoma Cervicis, is the most malignant tumor and is most often found in women. Acetic Acid Visual Inspection Examination (IVA) is an examination for cervical cancer examination. Indragiri Hulu Regency is the highest positive IVA district, at 17.85%, from the number of women aged 30-50 years who are positive suffering from cervical cancer. The purpose of this study was to study the description of the knowledge of women of fertile age (WUS) about the inspection of visual acetate acid inspection (IVA) in Sungai Air Putih Village, Indragiri Hulu Regency. The research design used descriptive design. The sampling technique used was purposive sampling and random  sampling with a total of 94 respondents. Data collection techniques by submitting questionnaires to married women of childbearing age (WUS) in Sungai Air Putih Village Sungai Lala Puskesmas Work Area in Indragiri Hulu Regency starting from 2-7 August 2018. Requesting research: finding inspection) less 63 WUS (67 %), enough 28 WUS (30%), and good 3 WUS (3%).                                                                     Kanker Serviks atau Carcinoma Cervicis Uteri, merupakan tumor yang paling ganas dan paling sering dijumpai pada wanita. Pemeriksaan Inspeksi Visual Asam Asetat (IVA) adalah pemeriksaan untuk mendeteksi gejala kanker serviks Tujuan penelitian untuk mengetahui gambaran pengetahuan Wanita Usia Subur (WUS) tentang pemeriksaan Inspeksi Visual Asam Asetat (IVA) di Desa Sungai Air Putih Kabupaten Indragiri Hulu.Desain penelitian menggunakan desain deskriptif. Teknik pengambilan sampel yang digunakan yaitu purposive sampling dan random sampling dengan jumlah 94 responden. Teknik pengambilan data dengan cara menyebarkan kuesioner pada Wanita Usia Subur (WUS) yang sudah menikah di Desa Sungai Air Putih Wilayah Kerja Puskesmas Sungai Lala Kabupaten Indragiri Hulu mulai dari 2-7 Agustus 2018.HAsil penelitian:pengetahuan tentang Pemeriksaan Inspeksi Visual Asam Asetat (IVA) adalah kurang 63 WUS (67%), cukup 28 WUS (30%), dan baik 3 WUS (3%).